2005
DOI: 10.1051/gse:2004033
|View full text |Cite
|
Sign up to set email alerts
|

Mapping quantitative trait loci for milk production and genetic polymorphisms of milk proteins in dairy sheep

Abstract: -In this paper, we present recent advances in the molecular dissection of complex traits in dairy sheep and discuss their possible impact on breeding schemes. In the first step, we review the literature data on genetic polymorphisms and the effects of sheep α s1 -casein and β-lactoglobulin loci. It is concluded that the results are rather inconsistent and cannot be used in dairy sheep selection. In a second step, we describe the strategy implemented in France, Italy and Spain taking advantage of the genetic ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 19 publications
2
45
0
2
Order By: Relevance
“…Furthermore, integrated analyses of both genetic map and radiation hybrid (RH) map indicated that the bovine FABP4 gene falls into the QTL interval for marbling on chromosome 14 (Michal et al, 2006). Interestingly, the same functional QTL has been detected on sheep chromosome 9, which is homologous to bovine chromosome 14 (Barillet et al, 2005). Hence, future studies should focus on mapping the sheep FABP4 gene and define the genetic basis of FABP4 effects on sheep meat quality traits.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, integrated analyses of both genetic map and radiation hybrid (RH) map indicated that the bovine FABP4 gene falls into the QTL interval for marbling on chromosome 14 (Michal et al, 2006). Interestingly, the same functional QTL has been detected on sheep chromosome 9, which is homologous to bovine chromosome 14 (Barillet et al, 2005). Hence, future studies should focus on mapping the sheep FABP4 gene and define the genetic basis of FABP4 effects on sheep meat quality traits.…”
Section: Discussionmentioning
confidence: 99%
“…Recent results demonstrate that there is genetic variation in sheep susceptibility to the disease (Fragkou et al, 2007) and that teeth disorders clearly favour mastitis inflammation in ewes (Mavrogianni and Fthenakis, 2007). QTL have been identified in traits that are known to influence mastitis susceptibility and resistance (Barillet et al, 2005). Also, genetic parameters and correlations indicated that udders with good shape are less prone to sub-clinical mastitis (Legarra and Ugarte, 2005).…”
Section: Mastitismentioning
confidence: 99%
“…Phenotypes were recorded for many traits from the secondgeneration backcross ewes. In addition to classical milk production traits, other phenotypes of interest in dairy sheep production such as milk fatty acid composition, kinetics of milk emission, udder morphology and resistance to mastistis and nematode infections were measured in this cross-population (Casu, 2004;Barillet et al, 2005;. Another remarkable research programme for QTL detection based on an experimental ovine population has been performed in Australia (CRC funded project).…”
Section: Cross-bred Experimental Populationsmentioning
confidence: 99%
“…French populations of Lacaune and Manech breeds have been studied following a granddaughter design, based on the large scale AI and progeny test performed as part of the breeding programmes of these breeds (Barillet et al, 2005). A total of 700 and 83 AI rams distributed in 22 families (18 in Lacaune and 4 in Manech breeds) were included in this QTL mapping population.…”
Section: Outbred Pedigreesmentioning
confidence: 99%
See 1 more Smart Citation